DHEA Supplementation Confers No Additional Benefit to that of Growth Hormone on Pregnancy and Live Birth Rates in IVF Patients Categorized as Poor Prognosis - Keane, Kevin N.; Hinchliffe, Peter M.; Rowlands, Philip K.; Borude, Gayatri; Srinivasan, Shanti; Dhaliwal, Satvinder S.; Yovich, John L. (Frontiers in Endocrinology, 2018)
Background: In Vitro Fertilisation (IVF) patients receive various adjuvant therapies in order to enhance success rates, but the true benefit is actively debated. Growth hormone (GH) and Dehydroepiandrosterone (DHEA) supplementation was assessed in women undergoing fresh IVF transfer cycles and categorised as poor prognosis from five criteria. Methods: Data was retrospectively analysed from 626 women undergoing 626 IVF cycles, where they received no adjuvant, GH alone or GH-DHEA in combination. A small group received DHEA alone. The utilisation of adjuvants was decided between the attending clinician and patient depending on various factors including cost. Results: Despite patients being significantly older with lower ovarian reserve, live birth rates were significantly greater with GH alone (18.6%) and with GH-DHEA (13.0%) in comparison to those with no adjuvant (p<0.003). No significant difference was observed between the GH groups (p=0.181). Overall, patient age, quality of the transferred embryo and GH treatment were the only significant independent predictors of live birth chance. Following adjustment for patient age, antral follicle count and quality of transferred embryo, GH alone and GH-DHEA led to a 7.1-fold and 5.6-fold increase in live birth chance, respectively (p<0.000). Conclusion: These data indicated that GH adjuvant may support more live births, particularly in younger women and importantly, the positive effects of GH treatment were still observed even if DHEA was also used in combination. However, supplementation with DHEA did not indicate any potentiating benefit or modify the effects of GH treatment. Due to the retrospective design, and the risk of a selection bias, caution is advised in the interpretation of the data.